ANALISIS FAKTOR PENGGUNAAN MARKETING MIX SEBAGAI PERTIMBANGAN KONSUMEN DALAM MEMILIH PAVING DI CV. OPEN ARTO MADURAN – LAMONGAN - Nawari Nawari; Siti Shoimah (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This research was conducted to find out what factors are considered by consumers in choosing Paving CV Open Arto. In Maduran Lamongan which is always crowded with visitors even though there are many other paving productions standing around Paving CV Open Arto.. The purpose of this study is to find out which factors are the most dominant consumers consider among the 7P product marketing mix variables, price, location, promotion, people, processes and physical evidence in the CV Open Arto. Maduran - Lamongan. The research method used in the CV Open Arto. is a quantitative method with a population of 4,320 visitors and 100 samples to be examined. This study uses factor analysis with SPSS and the results show that the dominant factor considered by consumers in choosing Paving is a person factor with an eigen value of 6,887 and the lowest factor is a product with an eigen value of 1,541.Keywoords: Marketing Mix, Consumer Considerations, Factor Analysis.